Abnormal Brain Structure Morphology in Early-Onset Schizophrenia - Cai, Jia; Wei, Wei; Zhao, Liansheng; Li, Mingli; Li, Xiaojing; Liang, Sugai; Deng, Wei; Du, Xiang Dong; Wang, Qiang; Guo, Wan-jun; Ma, Xiaohong; Sham, Pak C.; et al. (Frontiers in Psychiatry, 2022)
With less exposure to environmental and medication influences, individuals with early-onset schizophrenia (EOS) may provide valuable evidence to study the pathogenesis and phenotypic pattern of schizophrenia.T1-weighted magnetic resonance images were collected in 60 individuals with EOS and 40 healthy controls. Voxel-based morphometry and surface-based morphometry analyzes were performed. Gray matter volume, cortical thickness and cortical surface area were compared between the EOS and healthy controls and among schizophrenia subgroups (with or without family history of schizophrenia). Compared with healthy controls, the EOS group had reduced gray matter volume in the bilateral middle temporal gyrus and reduced cortical thickness in several brain regions. The sporadic early onset schizophrenia and the familial early onset schizophrenia showed different brain structure morphology. These findings suggest that abnormal brain structure morphology, especially in the temporal and frontal lobes, may be an important pathophysiological feature of EOS.